hsa_circ_0092306 Targeting miR-197-3p Promotes Gastric Cancer Development by Regulating PRKCB in MKN-45 Cells - Zihao Chen; Hongping Ju; Ting Zhao; Shan Yu; Ping Li; Jing Jia; Nan Li; Xiaojie Jing; Bibo Tan; Yong Li (Elsevier, 2019)
Gastric cancer (GC) is one of the most common cancers worldwide and is thus a global cancer burden. Here, we focused on a novel circular RNA hsa_circ_0092306 and explored the potential molecular mechanism to provide a new target for and novel insights into GC treatment. The GEO microarray was mined and analyzed with R software. Sanger sequencing and RNase R assay were applied to verify the identification of hsa_circ_0092306. Quantitative real-time PCR and western blot were performed to measure the mRNA and protein levels. Pull-down and luciferase reporter assays were conducted to confirm the target relationships. Annexin V-PI apoptosis flow cytometry, 3-(4,5Dimethylthiazol- yl)-2,5Dimethylthiazol-2-yl)-2,5diphenyltetrazolium bromide (MTT), wound healing, and Transwell assays were applied to detect cell apoptosis, viability, migration, and invasion in MKN-45 cells, respectively. A xenograft in vivo experiment was conducted to confirm the cell experiment results. hsa_circ_0092306 was upregulated in GC tissues and GC cells, and promoted GC development in MKN-45 cells. hsa_circ_0092306 inhibited tumor suppressor miR-197-3p expression but promoted tumor promotor protein kinase C beta (PRKCB) expression in MKN-45 cells. hsa_circ_0092306 and PRKCB had a common target (miR-197-3p) and were negatively related to miR-197-3p expression. hsa_circ_0092306 promoted the development of GC by regulating the pathway of miR-197-3p/PRKCB in MKN-45 cells. Keywords: gastric cancer, circular RNA, hsa_circ_0092306, miR-197-3p, PRKCB, protein kinase C beta